Analysis On Academic Information System Quality Toward User Satisfaction - Sultono, Sultono; Seminar, Kudong Boro; Erizal, Erizal (UI Scholars Hub, 2016)
Achieving excellent quality academic and administrative services is one of the efforts of the Indonesia University of Education (UPI) in building its Academic Information System (SIAK) under UPI Directorate of Information and Communication that was established on 6 July 2007. The use of Information and Communication Technology (TIK) for a system of information and academic services in higher education institution is an urgent necessity to increase the reputation of higher education institution both nationally and globally. This research aims to discover the relation, influences and analyzes the quality of academic information system quality toward user satisfaction in the Indonesia University of Education. The research use Gap Analysis and Structural Equation Model (SEM). Gap analysis results show a gap between performance and user expectation but average result of user satisfaction variable shows that respondents are satisfied with the academic information system implementation. SEM analysis result show that all research variables and indicators have significant relations, also that the academic information system quality (system quality, information quality and service quality (toward user satisfaction has a significant impact. Research discovery shows the necessity of periodical evaluation by the academic information system administrator with user participation, to ensure users need fulfillment.